2023
DOI: 10.1007/s00268-023-07020-6
|View full text |Cite
|
Sign up to set email alerts
|

Consensus Guidelines for Perioperative Care for Emergency Laparotomy Enhanced Recovery After Surgery (ERAS®) Society Recommendations Part 2—Emergency Laparotomy: Intra‐ and Postoperative Care

Abstract: Background This is Part 2 of the first consensus guidelines for optimal care of patients undergoing emergency laparotomy (EL) using an Enhanced Recovery After Surgery (ERAS) approach. This paper addresses intra‐ and postoperative aspects of care. Methods Experts in aspects of management of high‐risk and emergency general surgical patients were invited to contribute by the International ERAS® Society. PubMed, Cochrane, Embase, and Medline database searches were performed for ERAS elements and relevant specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 361 publications
(393 reference statements)
1
13
0
Order By: Relevance
“…By implementing fast-track protocol, patients in the modified ERAS group had a significant reduction in the time to pass first flatus and stool (p = 0.001 and p = 0.014 respectively). Additionally, liquid and solid diet was tolerated significantly earlier in these patients as also documented in previous studies [13,20,23,37]. In the elective context, the intra-abdominal drain is not routinely placed in the ERAS setting [38].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…By implementing fast-track protocol, patients in the modified ERAS group had a significant reduction in the time to pass first flatus and stool (p = 0.001 and p = 0.014 respectively). Additionally, liquid and solid diet was tolerated significantly earlier in these patients as also documented in previous studies [13,20,23,37]. In the elective context, the intra-abdominal drain is not routinely placed in the ERAS setting [38].…”
Section: Discussionsupporting
confidence: 60%
“…Although no difference in the incidence of UTI was seen between the two groups. In fast‐track protocol multimodal analgesia with regional blockade techniques used to alleviate post‐operative pain [37, 39]. In the present study, analgesia was dealt with at every step of ERAS care.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of surgical trauma, anaesthesia and tension, perioperative patients frequently have negative nitrogen balance. Early nutritional support of the intestines in the first few days after surgery is essential for assuring the success of the procedure 20 . Several studies have demonstrated that beginning nutritional support for the intestines as early as possible after surgery can enhance intestinal function recovery and nutritional status.…”
Section: Discussionmentioning
confidence: 99%
“…Early nutritional support of the intestines in the first few days after surgery is essential for assuring the success of the procedure. 20 Several studies have demonstrated that beginning nutritional support for the intestines as early as possible after surgery can enhance intestinal function recovery and nutritional status. The relationship between intestinal flora and wound recovery following CRC surgery is a subject of growing importance, especially considering the increase in surgical interventions for CRC and the critical role that the gut microbiota plays in overall health.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the first perioperative evidence-based ERASÒ Society guideline for emergency laparotomy (part 1) was published which included preoperative management in this surgical field [3]. In the current issue of the Journal, the two next parts (2 and 3) of the ERASÒ Society guidelines are published for intra-and postoperative care and the organizational aspects of emergency laparotomy, respectively [4,5]. Peden, Scott and colleagues are to be commended for these two important new consensus guidelines which are based on the best available evidence for a comprehensive ERAS approach in emergency laparotomy.…”
mentioning
confidence: 99%